Silver nanoparticles synthesized by in vitro derived plants and callus cultures of Clitoria ternatea; Evaluation of antimicrobial activity - Malabadi, Ravindra B.; Naik, Seema Lokare; T. Meti, Neelambika; S. Mulgund, Gangadhar; Nataraja, K.; Kumar, S. Vijaya (Research in Biotechnology, 2012)
This paper highlights for the first time the preparation and synthesis of silver nanoparticles from the callus and in vitro derived plant roots of white flowered variety of Clitora ternatea. The efficiency of antimicrobial activity of silver nanoparticles towards the clinical samples was assessed. Our study confirmed that these silver nanoparticles were found to be highly toxic and provides once again the pharmaceutical evidence of the medicinal plant Clitoria ternatea. Therefore, the use of silver nanoparticles should emerge as one of the novel approaches in many disease therapies, and applications of plant extract silver nanoparticles should be exploited for the medical treatment.